Conversazione in the Colonial Museum. Issue 1 (2nd January 2017) - Rice, R.
ABSTRACT: This article explores the role art played in popularising the activities of the Colonial Museum and science in nineteenth century Wellington. As the first state institution in New Zealand to collect material for the purposes of research and display, the Museum became both a repository for, and a generator of, art. It also served as a site for the exhibition of art, most notably at the conversazione held in association with the inaugural meeting of the New Zealand Institute in 1868. By the 1890s the miscellany of collections on show in the Museum led to it being dismissed as little more than a 'curiosity shop'. Yet arguably this diversity may have garnered public and professional support for the New Zealand Institute and Museum in the colonial context. By turning an eye to art within this setting we also begin to register the complex attitudes individuals such as Hector had towards art and science.